Lessons and Legacies XIV : The Holocaust in the Twenty-First Century; Relevance and Challenges in the Digital Age - Gigliotti, Simone; Cole, Tim, 1970- (Book collections on Project MUSE., 2021)
"This book reevaluates concepts such as Primo Levi's "gray zone" and uses digital methodologies to examine mobility and space and their relationship to hiding, resistance, and emigration, focusing on the histories of individuals and social groups"--